2021
DOI: 10.3324/haematol.2021.279895
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of SARS-CoV-2 infection in patients with monoclonal gammopathy of undetermined significance: a case-control study

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…We and others recently showed that patients with MGUS had the same risk of SARS‐CoV‐2 infection and a similar clinical outcome compared to age‐ and sex‐matched HCs during the first wave of the COVID‐19 pandemic, before the availability of anti‐SARS‐CoV‐2 vaccines 9,10 . Here, we report that fully vaccinated individuals with MGUS maintain an analogous incidence of SARS‐CoV‐2 infection, but also show a significant improvement in clinical outcomes of COVID‐19 compared to not vaccinated patients, formally proving, for the first time, the efficacy of anti‐SARS‐CoV‐2 vaccines in this population of patients.…”
Section: Prevaccinationa Postvaccination P Valuesupporting
confidence: 72%
See 1 more Smart Citation
“…We and others recently showed that patients with MGUS had the same risk of SARS‐CoV‐2 infection and a similar clinical outcome compared to age‐ and sex‐matched HCs during the first wave of the COVID‐19 pandemic, before the availability of anti‐SARS‐CoV‐2 vaccines 9,10 . Here, we report that fully vaccinated individuals with MGUS maintain an analogous incidence of SARS‐CoV‐2 infection, but also show a significant improvement in clinical outcomes of COVID‐19 compared to not vaccinated patients, formally proving, for the first time, the efficacy of anti‐SARS‐CoV‐2 vaccines in this population of patients.…”
Section: Prevaccinationa Postvaccination P Valuesupporting
confidence: 72%
“…Clinical characteristics of not vaccinated MGUS have been previously reported in detail 9 and are summarized and compared with those of vaccinated patients in Table 1. Of the 86 vaccinated SARS‐CoV‐2‐positive patients, 53 (61.6%) were men, while the mean (SD) age was 65.9 (±13.4) years.…”
Section: Prevaccinationa Postvaccination P Valuementioning
confidence: 99%
“… 4 This aligns with reported data that MGUS patients did not show an increased incidence of SARS-CoV-2 infection compared to the general population and that MGUS did not appear to represent a risk for a poorer COVID-19 outcome. 11 , 12 Indeed, in our previous experience, vaccination improved COVID-19 outcome, but not SARS-CoV-2 incidence. 13 Second, to date it is the only study to report a long persistence (until 180 days) of anti-spike IgG antibodies after “booster” dose in MGUS patients, although a clear-cut relationship between these antibodies and protection against the virus have not been unequivocally established.…”
mentioning
confidence: 87%
“…In contrast to the markedly increased risk from SARS-CoV-2 infection in myeloma patients, a recent retrospective study [6] examined the prevalence of COVID-19 among a group of 1454 patients with MGUS. Out of the 91 patients who tested positive for the virus using RT-PCR on nasopharyngeal swabs between 1 March 2020 and 30 April 2021, the authors found that those with MGUS were equally susceptible to the infection and had similar outcomes as healthy controls of the same age and gender during the initial wave of the COVID-19 pandemic.…”
Section: Clinical Features Of MM Patients With Sars-cov-2 Infectionmentioning
confidence: 99%